Bilateral facial nerve palsy associated with HIV seroconversion illness. Issue 992 (21st July 2008) - Yeo, J C L; Trotter, M I; Wilson, F
Abstract : Bilateral facial nerve palsy is a rare but recognised manifestation of HIV seroconversion illness. The pathophysiology of this clinical presentation is thought to be associated with the immune response of the dissemination of virus throughout the body. We describe a case of bilateral facial nerve palsy, subsequently diagnosed with HIV. Related medical literature is also reviewed. The case highlights the vigilance required in unusual, atypical signs and symptoms if a diagnosis of HIV infection is not to be missed. Clinicians should be aware of the potential presentation of HIV seroconversion illness to provide opportunity for early diagnosis and intervention.